Effects of different ischemic preconditioning occlusion pressures on muscle damage induced by eccentric exercise: a study protocol for a randomized controlled placebo clinical trial - Pizzo Junior, Eduardo [UNESP]; de Souza Cavina, Allysiê Priscilla [UNESP]; Lemos, Leonardo Kesrouani [UNESP]; Biral, Taíse Mendes [UNESP]; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Franciele Marques [UNESP] (Springer Nature, 2021)
Introduction: Due to its greater generation of muscle strength and less metabolic demand, eccentric exercise has been widely used in rehabilitation and for improving physical fitness. However, eccentric exercise can induce muscle damage by providing structural changes and reduced muscle function, so even with the protection caused by the repeated bout effect from eccentric exercise, it is necessary to seek alternatives to reduce this damage caused by stress. Thus, ischemic preconditioning could represent an aid to reduce the damage muscle or increase the protective effect caused by eccentric exercise. Objectives: To compare the effects of ischemic preconditioning, using different occlusion pressures, on acute and delayed responses to perceptual outcomes, markers of muscle damage, and performance in post-eccentric exercise recovery. Methods: A randomized controlled placebo clinical trial will be carried out with 80 healthy men aged 18 to 35 years who will be randomly divided into four groups: ischemic preconditioning using total occlusion pressure, ischemic preconditoning with 40% more than total occlusion pressure, placebo (10 mmHg), and control. The ischemic preconditioning protocol will consist of four cycles of ischemia and reperfusion of five minutes each. All groups will perform an eccentric exercise protocol, and assessments will be carried out before, immediately after, and 24, 48, 72, and 96 h after the end of the eccentric exercise to evaluate creatine kinase, blood lactate, perception of recovery using the Likert scale, being sequentially evaluated, pain by the visual analog scale, pain threshold using a pressure algometer, muscle thickness by ultrasound, muscle tone, stiffness and elasticity by myotonometry, vectors of cell integrity through electrical bioimpedance, and maximal voluntary isometric contraction using the isokinetic dynamometer. The trial was registered at ClinicalTrials.gov (NCT04420819). Discussion: The present study aims to present an alternative technique to reduce muscle damage caused by eccentric exercise, which is easy to apply and low cost. If the benefits are proven, ischemic preconditioning could be used in any clinical practice that aims to minimize the damage caused by exercise, presenting an advance in the prescription of eccentric exercise and directly impacting on the results of post-exercise recovery. Trial registration: ClinicalTrials.gov NCT04420819. Registered on 19 May 2020; Last update 24 March 2021.
Keywords: Creatine kinase; Exercise; Ischemic preconditioning; Muscle fatigue; Musculoskeletal pain; Physiological; Randomized controlled trial; Stress